2021
DOI: 10.1080/02656736.2021.1963850
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results of PTMC treated by ultrasound-guided radiofrequency ablation: a retrospective study

Abstract: Objectives: To confirm the long-term efficacy and safety of radiofrequency ablation (RFA) for low-risk papillary thyroid microcarcinoma (PTMC). Methods: We retrospectively reviewed data of 102 primary papillary thyroid carcinoma patients (82 women, 20 men; mean age: 43 [19] years) treated with radiofrequency ablation and thyroid-stimulating hormone (TSH) suppression therapy before December 2018. All patients were at high surgical risk or refused surgery. They were followed up at 1, 3, 6, 9, and 12 months and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Radiofrequency ablation (RFA) is one treatment option that has demonstrated impressive safety and efficacy profiles [ 56 , 57 ]. A 2021 study of 102 patients with PTMC found 100% resorption rates at the 5-year follow-up [ 58 ]. Befittingly, minimally invasive ablative technology is generally more efficacious in nodules of smaller sizes [ 59 , 60 ], making them an attractive option for patients with PTMC.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is one treatment option that has demonstrated impressive safety and efficacy profiles [ 56 , 57 ]. A 2021 study of 102 patients with PTMC found 100% resorption rates at the 5-year follow-up [ 58 ]. Befittingly, minimally invasive ablative technology is generally more efficacious in nodules of smaller sizes [ 59 , 60 ], making them an attractive option for patients with PTMC.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 339 thermal ablation and 314 surgical patients (54) showed no statistically significant differences in the rates of local tumor recurrence, lymph node metastasis, distant metastasis, and salvage surgery between surgery and ablation. In a long-term follow-up study (27), two patients treated with thermal ablation developed ipsilateral cervical lymph node metastases; however, a study by Myung et al (55) showed a recurrence rate of 1.4% in patients followed for 5-6 years after surgery. By contrast, ablation does not affect the prognosis of patients treated with or without surgery, and it preserves at least one side of the thyroid gland in most patients.…”
Section: A Comparative Study Of Thermal Ablation Versus Surgical Proc...mentioning
confidence: 95%
“…Cho et al (26) reported complete disappearance rates of 98.8% and 100% at 24 and 60 months after RFA for PTMC, respectively, with no local tumor progression, lymph node metastasis, distant metastasis, delayed complications, surgery-related death, or delayed surgery. A 5-year retrospective study of RFA for PTMC was also conducted in China (27), and all nodes were completely absorbed at the end of follow-up, with only 2 patients developing ipsilateral lateral cervical lymph node metastasis. These studies confirm the effectiveness and safety of RFA for the treatment of PTMC.…”
Section: Rfamentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, minimally invasive image-guide ablation techniques such as microwave ablation (MWA), radiofrequency ablation (RFA), laser ablation (LA) have been developed. The outcomes of thermal ablation for unifocal PTMC were proved to be promising according to the previous studies (9)(10)(11).However, the study on MWA of multifocal PTMC has seldom been reported.…”
Section: Introductionmentioning
confidence: 86%